2011
DOI: 10.1074/jbc.m111.247478
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Inactivates Melastatin Transient Receptor Potential 2 Channels via the Outer Pore

Abstract: Zinc ion (Zn 2؉ ) is an endogenous allosteric modulator that regulates the activity of a wide variety of ion channels in a reversible and concentration-dependent fashion. Here we used patch clamp recording to study the effects of Zn 2؉ on the melastatin transient receptor potential 2 (TRPM2) channel. Zn 2؉ inhibited the human (h) TRPM2 channel currents, and the steady-state inhibition was largely not reversed upon washout and concentration-independent in the range of 30 -1000 M, suggesting that Zn 2؉ induces c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 80 publications
0
34
2
Order By: Relevance
“…Since extracellular Ca 2 + entry potentiates ROS-induced Zn 2 + release and Ca 2 + is an activator of TRPM2 channels [32,33], we propose that extracellular Ca 2 + enters through the plasma membrane TRPM2 channels and co-stimulates (together with H 2 O 2 ) lysosomal TRPM2 channels to promote Zn 2 + release ( Figure 4E). Although TRPM2-channel-mediated Zn 2 + influx could be demonstrated in HEK-293 cells using FluoZin-3 [19], our attempts to demonstrate Zn 2 + permeation by electrophysiology have been unsuccessful [46], largely because concentration of Zn 2 + required to demonstrate Zn 2 + currents were found to inhibit the channel profoundly.…”
Section: Discussionmentioning
confidence: 99%
“…Since extracellular Ca 2 + entry potentiates ROS-induced Zn 2 + release and Ca 2 + is an activator of TRPM2 channels [32,33], we propose that extracellular Ca 2 + enters through the plasma membrane TRPM2 channels and co-stimulates (together with H 2 O 2 ) lysosomal TRPM2 channels to promote Zn 2 + release ( Figure 4E). Although TRPM2-channel-mediated Zn 2 + influx could be demonstrated in HEK-293 cells using FluoZin-3 [19], our attempts to demonstrate Zn 2 + permeation by electrophysiology have been unsuccessful [46], largely because concentration of Zn 2 + required to demonstrate Zn 2 + currents were found to inhibit the channel profoundly.…”
Section: Discussionmentioning
confidence: 99%
“…Whether Zn 2+ plays a similar role in cell migration induced by other migration-promoting signals, and in the migration of other cell types, remains to be investigated. Furthermore, although a role for the TRPM2 channel, and for Zn 2+ , are clear, and H 2 O 2 -induced elevation of cytoplasmic Zn 2+ could be demonstrated using fluorescent probes, it has proved difficult to demonstrate permeability of the channel to Zn 2+ by electrophysiology (Manna et al, 2015;Yang et al, 2011). Thus, mechanisms other than direct Zn 2+ permeation by the channel cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TRPA1 is activated by about 20 M ZnCl 2 , and TRPM1 is inhibited by high concentrations (mM) of ZnCl 2 (18,19). TRPM2 is inactivated by more than 30 M ZnCl 2 , and Zn 2ϩ entering cells through TRPM7 channel is involved in Zn 2ϩ -mediated neuronal injury (20,21). In this study, we found extracellular Zn 2ϩ to be a potential blocker of TRPM5 activity.…”
Section: Transient Receptor Potential Melastatin 5 (Trpm5)mentioning
confidence: 77%